The association between Urban and Rural Resident Basic Medical Insurance and instrumental activity of daily living disability among middle-aged and older adults in China - Jian Sun; Shui Yu; Wanjun Lu; Yujiang Liu (BMC, 2023)
Abstract Background Previous studies have not investigated the association between medical insurance and instrumental activity of daily living (IADL) disability. To fulfill this research gap, this study aims to explore the association between Urban and Rural Resident Basic Medical Insurance (URRBMI) and IADL disability among middle-aged and older adults in China. Methods The data of this study were sourced from the 2018 wave of China Health and Retirement Longitudinal Study (CHARLS). Logit regression models were used to analyze the association between URRBMI and odds of suffering from IADL disability. Furthermore, we used IV-Probit regression model to address the potential endogeneity problem. Moreover, propensity score matching and generalized random forest model were employed to conduct robustness checks. Results The logit regression results reveal that URRBMI participation was significantly related to reduced odds of suffering from IADL disability by 39.86% after adjusting for the control variables (p < 0.01). The results of IV-Probit estimation show that URRBMI was an exogenous variable. Further robustness checks reported similar estimation results. The results of heterogeneity analysis reveal that URRBMI produced a statistically stronger effect on IADL disability for the older adults (OR = 0.5815, p < 0.01) when compared with the middle-aged adults (OR = 0.5690, p < 0.05). The results of impact channel analysis indicate that physical exercise was a channel involving the effect of URRBMI on IADL disability. Conclusion This study finds that the middle-aged and older adults who were covered by URRBMI had a reduced possibility of suffering from IADL disability when compared with those without URRBMI. Furthermore, it is found that URRBMI produced a statistically stronger effect on IADL disability for the older adults when compared with the middle-aged adults. Moreover, we obtain evidence indicating that physical exercise was a channel involving the effect of URRBMI on IADL disability.